Grey-Scale Analysis Improves the Ultrasonographic Evaluation of Thyroid Nodules. Issue 27 (July 2015) - Grani, Giorgio; D'Alessandri, Mimma; Carbotta, Giovanni; Nesca, Angela; Del Sordo, Marianna; Alessandrini, Stefania; Coccaro, Carmela; Rendina, Roberta; Bianchini, Marta; Prinzi, Natalie; Fumarola, Angela; Malhotra., Gaurav
<x xml:space="preserve">Abstract</x> Abstract Ultrasonography is the main imaging method for the workup of thyroid nodules. However, interobserver agreement reported for echogenicity and echotexture is quite low. The aim of this study was to perform quantitative measurements of the degree of echogenicity and heterogeneity of thyroid nodules, to develop an objective and reproducible method to stratify these features to predict malignancy. A retrospective study of patients undergoing ultrasonography-guided fine-needle aspiration was performed in an University hospital thyroid center. From January 2010 to October 2012, 839 consecutive patients (908 nodules) underwent US-guided fine-needle aspiration. In a single ultrasound image, 3 regions of interest (ROIs) were drawn: the first including the nodule; the second including a portion of the adjacent thyroid parenchyma; the third, the strap muscle. Histogram analysis was performed, expressing the median, mean, and SD of the gray levels of the pixels comprising each region. Echogenicity was expressed as a ratio: the nodule/parenchyma, the nodule/muscle, and parenchyma/muscle median gray ratios were calculated. The heterogeneity index (HI) was calculated as the coefficient of variation of gray histogram for each of the 3 ROIs. Cytology and histology reports were recorded. Nodule/parenchyma median gray ratio was significantly lower (more hypoechoic) in nodules found to be malignant (0.45 vs 0.61; P = 0.002) and can be used as a continuous measure of hypoechogenicity (odds ratio [OR] 0.12; 95% confidence interval [CI] 0.03–0.49). Using a cutoff derived from ROC curve analysis (<0.46), it showed a substantial inter-rater agreement (k = 0.74), sensitivity of 56.7% (95% CI 37.4–74.5%), specificity of 72.0% (67.8–75.9%), positive likelihood ratio (LR) of 2.023 (1.434–2.852), and negative LR of 0.602 (0.398–0.910) in predicting malignancy (diagnostic odds ratio 3.36; 1.59–7.10). Parenchymal HI was associated with anti-thyroperoxidase positivity (OR 19.69; 3.69–105.23). The nodule HI was significantly higher in malignant nodules (0.73 vs 0.63; P = 0.03) and, if above the 0.60 cutoff, showed sensitivity of 76.7% (57.7–90.1%), specificity of 46.8% (42.3–51.4%), positive LR of 1.442 (1.164–1.786), and negative LR of 0.498 (0.259–0.960). Evaluation of nodule echogenicity and echotexture according to a numerical estimate (nodule/parenchyma median gray ratio and nodule HI) allows for an objective stratification of nodule echogenicity and internal structure.